Northern Landscapes : ʻʻImplementation of the European Landscape Convention In the North Calotte Area Municipalitiesʼʼ - Conference in Inari, Finland 7-9.9.2011 - Raasakka, Noora (toim.); Sivonen, Sari (toim.) (Lapin ELY-keskus, 2012)
The conference promoting the objectives of the international European Landscape Convention (ELC) was held on 7-9 September 2011 in Inari. The primary aim of the conference was to increase awareness of the ELC and the prospects and requirements it brings to practical planning work, especially at the municipal level. The conference speakers included top experts from Sweden, Norway, Finland, France, Holland and Catalonia. This report is a collection of articles written by the experts in the ELC conference. The report is available in five languages: Finnish, Swedish, Norwegian, Northern Sámi and English. The common characteristics of the North Calotte area, such as the magnificent riverside scenery and the beautiful fell landscapes formed by the Sámi culture and reindeer management are broadly reflected in the environment. Alongside the traditional forms of land use, many other livelihoods and forms of land use now need to be accommodated in the area. Tourism, energy production, mining industry and new infrastructure create new and manifold challenges to the authorities in charge of land use in these areas. Municipalities need information and support for versatile planning in the future, so that the unique and valuable characteristics of the North can be preserved. Landscape protection and management in the landscape areas is executed through areal and land use planning, mainly through town planning and the creation of landscape management plans. The municipalities in the North Calotte region have their own partly divergent methods and practices, based on the various land use processes are executed. The municipalities and inhabitants have a great interest in preserving and protecting their living environment and maintaining and increasing the appeal of the area. Landscape is viewed as one of the most significant appealing factors that cannot be lost. The increasing land use in municipalities, for example due to energy production, mining industry and increasing tourism, create a need for more multidimensional ...